‘I’m not just a vet, I’m also a human.’ A qualitative interview study on boundary management between work and private life among small animal veterinarians - Christian Dürnberger; Svenja Springer (PLoS ONE, 2025)
Introduction Many studies of veterinarians underline the importance of work-life balance, yet our understanding of how veterinarians manage the boundary between private and professional life is still limited. In line with previous research that speaks of “boundary management” in this context, it is the overall aim of this study to investigate the conflicts and challenges veterinarians face in relation to temporal, physical and psychological boundaries between work and private life, and to explore the coping strategies they employ to navigate these challenges. Methods The study is based on qualitative, semi-structured individual focused interviews with 20 small animal veterinarians resident in Germany (n = 8), Switzerland (n = 7) and Austria (n = 5), who specialised in the field of hospice and palliative care. A structured coding process, incorporating both deductive and inductive elements, was utilized to analyse the data through two cycles of coding, thereby identifying key themes. Results The study identified that the veterinarians have to deal with conflicting private and professional appointments, accessibility outside of opening hours through information and communication technologies, professional concerns occupying the veterinarian’s private life and unwanted insights into the animal owners’ lives. Coping strategies show that veterinarians are willing to integrate professional aspects into their private lives and accept accompanying negative consequences because they are convinced that they are acting in the best interest of the animals. At the same time, boundary management for veterinarians means a conscious demarcation from the animal owner along temporal, physical and psychological boundaries, e.g., ensuring that the relationship remains a professional business relationship and does not become too personal. In addition, our data suggest that previous negative experiences of a lack of work-life balance led to stricter boundaries and more of a “self-care” mindset.